2012
DOI: 10.1128/aac.01794-12
|View full text |Cite
|
Sign up to set email alerts
|

Ceftaroline versus Isolates from Animal Bite Wounds: Comparative In Vitro Activities against 243 Isolates, Including 156 Pasteurella Species Isolates

Abstract: bMore than 5 million Americans are bitten by animals, usually dogs, annually. Bite patients comprise ϳ1% of all patients who visit emergency departments (300,000/year), and approximately 10,000 require hospitalization and intravenous antibiotics. Ceftaroline is the bioactive component of the prodrug ceftaroline fosamil, which is FDA approved for the treatment of acute bacterial skin and skin structure infections (ABSSSIs), including those containing methicillin-resistant Staphylococcus aureus (MRSA). There are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Although P. multocida is frequently reported in feline oral microbiota and isolated in cat bites ( Goldstein et al , 2012 ), the literature contains no data about the occurrence, presence of virulence genes or resistance profiles in P. multocida strains from cats in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Although P. multocida is frequently reported in feline oral microbiota and isolated in cat bites ( Goldstein et al , 2012 ), the literature contains no data about the occurrence, presence of virulence genes or resistance profiles in P. multocida strains from cats in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobials selected for therapy of infected animal bite wounds must have activity against the components of the biting animals' oral flora, including P. multocida and its subspecies. 15 Recommendations about case selection for antibiotic prophylaxis may vary. Currently recommended regimens include amoxicillin-clavulanic acid orally or ampicillin-sulbactam, carbapenems, or cefoxitin intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that ceftiofur sodium exerts bactericidal effect on tested microorganisms at concentration equal to or at most one doubling dilution above MIC. Many authors were reportedthat high activity of ceftiofur against P. multocida isolated from cattle, swine and duck in vitro [10,12,28,29]. Also, some authors [8] reported that the MIC of ceftiofur sodium required to inhibit growth of 90% of isolates of E. coli, Pasteurella spp., Klebsiella spp., and beta-haemolytic Streptococci was <0.5 microg/ml, and intravenous administration of ceftiofur sodium at rate of 5 mg/kg every 12 h would provide sufficient coverage for the treatment of susceptible bacterial isolates.…”
Section: Discussionmentioning
confidence: 99%
“…First group received Salmonella gallinarum with an intraperitoneal inoculation of infective dose 6 × 10 4 viable cells [16][17][18][19]. Chicks of second group succumbed to an artificial infection with P. multocida with an intramuscular dose of 1 × 10 4 viable cells/ml [10,20], while each chick of third group was intravenously inoculated with 0.1 ml of broth culture of E. coli containing 10 8 viable cells/ml [21]. All inoculated and control birds were daily observed and reared under strict hygienic measures.…”
Section: Determination Of Antimicrobial Agentsmentioning
confidence: 99%
See 1 more Smart Citation